Wire Electrical Discharge Machining of Tungsten Carbide - Mas Ayu, Hassan (2008)

(untitled)
This paper presented a study on the machining of tungsten carbide (WC-15%Co) using wire electro-discharge machining (WEDM) with brass wire diameter of 0.2 mm used as the tool electrode. The main purposes of this study is to investigate the influenced of various parameters involved in WEDM on the machining characteristics, namely, sparking gap (Gap), cutting speed (CS) and microstructure after undergone WEDM process. The Full Factorial Design of Experiment (DOE) method with two-level was used to formulate the experimental layout, to analyze the effect of each parameter on the machining characteristics and to predict the optimal setting for each WEDM parameters such as pulse on (ON), pulse off (OFF), peak current (IP) and servo voltage (SV). Confirmation tests were also conducted for the optimum conditions for each machining characteristics, in order to verify and compared the results from the theoretical prediction (Design Expert) and experimental confirmation tests. In this investigation, the machining operation for tungsten carbide is performed using Sodick linear motor WEDM series AQ537L. Meanwhile, for the measurement equipments; Zeiss Axiotech High Power Optical Microscope is used to measure Gap and to examine the microstructures of the machined surface, Scanning Electron Microscope XL40 is carried out. Analysis done by DOE method reveals that in general, pulse on has appeared to be significant effect to all three responses investigated in this research. Overall, the results from the confirmation tests showed that the percentage of performance is acceptable due to all the results obtained were within the allowable values which is less than 10% of margin error.